Trade in Artists’ Materials. Markets and Commerce in Europe to 1700. - Calvo Manuel, Ana (Ge-conservacion, 2011)
Reseña del libro:Trade in Artists’ Materials. Markets and Commerce in Europe to 1700. Edited by Jo Kirby, Susie Nash y Joanna Cannon Archetype Publications Ltd. Londres, 2010 509 páginas, ilustraciones en color y blanco y negro, 297 x 210 mm., pasta dura ISBN: 978-1-904982-25-8